Shape memory paranasal sinus stent and preparation method thereof

By designing the cylindrical hollow structure and multi-layer drug-loading membrane of the shape memory sinus stent, the strength and compatibility problems of traditional sinus stents are solved, better mechanical properties and biocompatibility are achieved, and foreign body sensation and displacement are reduced. Risk, providing sequential dosing and intelligent controlled release.

CN119279877APending Publication Date: 2025-01-10HARBIN INST OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411403776.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The radial support strength of traditional sinus drug stents is poor and has poor biocompatibility with the human body, making it easy to displace or discharge after implantation.

Method used

A shape memory sinus stent was designed, which is made of shape memory polylactic acid, biomedical polymer materials and plasticizers, with a cylindrical hollow structure, covered with electrospinned nanomedicine-loaded fiber membrane and hydrogel-loaded The pharmaceutical fiber membrane, the stent can change from a temporary shape to an initial shape under external stimulation, enhancing mechanical properties and reducing foreign body sensation.

Benefits of technology

The radial support strength of the sinus stent is improved, the risk of foreign body sensation and displacement is reduced, sequential administration and intelligent controlled release of drugs are achieved, the fit with the inner wall of the sinus is enhanced, and the discomfort is reduced after surgery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119279877A_ABST
    Figure CN119279877A_ABST
Patent Text Reader

Abstract

The invention provides a shape memory paranasal sinus stent. The paranasal sinus stent comprises a stent body, an electrostatic spinning nano drug-loaded fibrous membrane and a hydrogel drug-loaded fibrous membrane, wherein the electrostatic spinning nano drug-loaded fibrous membrane and the hydrogel drug-loaded fibrous membrane sequentially cover the outer surface of the stent body; wherein the stent body has a temporary shape and an initial shape, and the initial shape of the stent body is composed of a plurality of annular supporting pieces and a plurality of connecting pieces located between every two adjacent annular supporting pieces; each annular supporting piece is of a sine wave structure, wave crests and wave troughs of sine waves of every two adjacent annular supporting pieces correspond to each other, and the wave crests and the wave troughs, close to each other, of the sine waves are connected through connecting pieces every other pair of corresponding wave crests and wave troughs, so that the initial shape of the stent body is of a cylindrical hollow structure; when the shape memory paranasal sinus stent is stimulated by the outside, the shape memory paranasal sinus stent can be converted into an initial shape with a large size from a temporary shape with a small size. The paranasal sinus drug stent in the scheme has high radial supporting strength and good compatibility with the human body, and displacement is not prone to occurring when the paranasal sinus drug stent is implanted into the human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical instruments and in particular to a shape memory sinus stent and a preparation method thereof. Background Art

[0002] Chronic rhinosinusitis (CRS) is a chronic inflammatory disease that occurs in the nasal cavity and sinus mucosa, with increased nasal secretions, nasal obstruction, headache and other symptoms as the main symptoms. Functional endoscopic sinus surgery is the preferred surgical treatment for CRS. It can remove irreversible lesions in the nasal cavity and sinuses of patients with chronic sinusitis and restore them to normal structural morphology. Due to problems such as postoperative management and compliance, there are adverse reactions such as adhesion, restenosis, scar formation, polyp recurrence and persistent inflammation, resulting in about 20% of CRS patients needing surgery again; the degradable sinus drug stent can be accurately implanted and support the sinus opening, and can continuously and quantitatively release hormone drugs, which can make up for the deficiencies after surgery to a certain extent.

[0003] In the related art, the main body material of the sinus drug stent is usually made of shape memory polylactic acid copolymer. However, the mechanical properties of polymer materials are weaker than those of metal materials used in traditional stents. Under the same structure, the radial support strength of the degradable polymer stent is much smaller than that of the metal stent and may not even meet clinical needs. In addition, the poor biocompatibility of the stent main body material with the human body can easily cause patients to feel a foreign body sensation and discomfort, and it is very easy to cause displacement or expulsion after implantation in the human body.

[0004] Therefore, based on the above problems, there is an urgent need to provide a shape memory sinus stent and a preparation method thereof. Summary of the invention

[0005] The embodiment of the present invention provides a shape memory sinus stent and a preparation method thereof, which can solve the problems of poor radial support strength, poor compatibility with the human body and easy displacement or expulsion when implanted in the human body of traditional sinus drug stents.

[0006] In a first aspect, the present invention provides a shape memory sinus stent, comprising a stent body and an electrospun nano drug-loaded fiber membrane and a hydrogel drug-loaded fiber membrane sequentially coated on the outer surface of the stent body; wherein the stent body comprises a temporary shape and an initial shape, and the initial shape of the stent body is composed of a plurality of annular support members and a plurality of connecting members located between two adjacent annular support members; each annular support member presents a sinusoidal wave structure, the crests and troughs of the sinusoidal waves of two adjacent annular support members correspond to each other, and the connecting members connect the crests and troughs of the sinusoidal waves that are close to each other every pair of corresponding crests and troughs, so that the initial shape of the stent body presents a cylindrical hollow structure;

[0007] The size of the temporary shape of the stent body is smaller than the size of the initial shape of the stent body, and the shape memory sinus stent can be transformed from the temporary shape to the initial shape when subjected to external stimulation.

[0008] Preferably, the connecting member includes a first connecting portion and a second connecting portion, the first connecting portion is "S"-shaped, the second connecting portion is "V"-shaped, and two adjacent annular support members are alternately connected through the first connecting portion and the second connecting portion.

[0009] More preferably, the starting point and end point of the "S"-shaped first connecting portion are respectively connected to the crests and troughs of two adjacent support members, and the starting point and end point of the "V"-shaped second connecting portion are respectively connected to the crests and troughs of two adjacent support members.

[0010] Preferably, the heights of two adjacent wave peaks in the sine wave of each annular support member are different.

[0011] Preferably, the raw materials for preparing the stent body include shape memory polylactic acid, biomedical polymer materials, and plasticizers; wherein the biomedical polymer material is at least one of glycolic acid-lactic acid copolymer, polycaprolactone, polyethylene glycol, polysuccinic acid co-succinate, polyglycolic acid, polytrimethylene carbonate, polypara-dioxanone, or polyvinyl alcohol, and the plasticizer is at least one of vegetable oil-based plasticizers, plant-based plasticizers, bio-based plasticizers, or citrate plasticizers.

[0012] More preferably, the raw material for preparing the stent body further includes a driving agent, and the driving agent is at least one of hollow copper sulfide particles, gold nanoparticles, and carbon-based nanomaterials.

[0013] Preferably, the raw materials for preparing the electrospun nano drug-loaded fiber membrane include shape memory polylactic acid, biomedical polymer materials, additives and therapeutic drugs; wherein the additive is at least one of Centella asiatica, onion extract, chitosan, silk fibroin or chitosan, and the therapeutic drug is at least one of mometasone furoate, triamcinolone acetonide, budesonide, fluticasone propionate or beclomethasone propionate.

[0014] Preferably, the raw materials for preparing the hydrogel drug-loaded fiber membrane include natural polymer materials and therapeutic drugs; wherein the natural polymer material is at least one of chitosan, silk fibroin, sodium alginate, gelatin, hyaluronic acid, chitin or collagen.

[0015] Preferably, the degradation rates of the electrospun nano drug-loaded fiber membrane, the hydrogel drug-loaded fiber membrane and the stent body are different from each other.

[0016] More preferably, the degradation rates of the hydrogel drug-loaded fiber membrane, the electrospun nano drug-loaded fiber membrane and the stent body decrease in sequence.

[0017] In a second aspect, the present invention provides a method for preparing the shape memory sinus stent as described in any one of the first aspects above, the preparation method comprising the following steps:

[0018] (1) constructing a three-dimensional structural model of the initial shape of the stent body according to the shape and size of the sinus structure;

[0019] (2) mixing shape memory polylactic acid with a biomedical polymer material to obtain a shape memory polymer, and performing 4D printing according to the three-dimensional structure model using the shape memory polymer as a printing line to obtain a stent body of an initial shape;

[0020] (3) preparing an electrospun nano drug-loaded fiber membrane and a hydrogel drug-loaded fiber membrane respectively by an electrospinning method, and coating the electrospun nano drug-loaded fiber membrane and the hydrogel drug-loaded fiber membrane on the surface of the stent body in sequence to obtain a shape memory sinus stent of an initial shape;

[0021] (4) The shape memory sinus stent of the initial shape is heated to above the glass transition temperature, a load is applied, and the shape memory sinus stent of the temporary shape is obtained after cooling and shaping.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] (1) In the present invention, the initial structure of the stent body is first designed as a cylindrical hollow structure, which is composed of a plurality of unequal height annular support members in the form of a sine wave and a plurality of connecting members, and the crests and troughs of the sine waves of two adjacent annular support members correspond to each other, and the crests and troughs of the sine waves that are close to each other are connected by connecting members every pair of corresponding crests and troughs, so that the shape memory sinus stent of the structure has better mechanical properties and stronger radial support capacity;

[0024] (2) In the present invention, by further sequentially arranging electrospun nano drug-loaded fiber membranes and hydrogel drug-loaded fiber membranes for carrying different therapeutic drugs on the surface of the stent body, different types of fiber membranes can not only deliver drugs immediately after surgery, but also achieve sequential drug delivery and intelligent controlled drug release; at the same time, when in use, the hydrogel drug-loaded fiber membrane first contacts the inner wall of the human sinus, thereby greatly reducing the discomfort and foreign body sensation of the human body, and at the same time, due to its certain adhesion, it can also effectively avoid the problem of displacement or expulsion of the stent body;

[0025] (3) The size parameters of the sinus stent in the present invention can be adjusted according to the human sinus structure, and can be customized; and the stent body has shape memory properties. When the stent is in a temporary shape, the size is small and convenient for implantation. When subjected to external stimuli, the stent body can be transformed from the temporary shape to the larger initial shape. In the process of shape memory recovery, due to the resistance of the inner wall of the sinus, the shape memory sinus stent can be completely fitted with the inner wall of the sinus, thereby reducing the patient's foreign body sensation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 It is a schematic diagram of the overall structure of a shape memory sinus stent provided by one embodiment of the present invention;

[0028] Figure 2 It is a schematic diagram of the initial shape structure of a stent body in a shape memory sinus stent provided by one embodiment of the present invention;

[0029] Figure 3 It is a physical diagram of the initial shape structure of a stent body in a shape memory sinus stent provided by one embodiment of the present invention;

[0030] Figure 4 It is a physical diagram of a temporary shape structure of a stent body in a shape memory sinus stent provided by one embodiment of the present invention;

[0031] Figure 5 It is a schematic structural diagram of a stent body and an electrospun nano drug-loaded fiber membrane in a shape memory sinus stent provided by one embodiment of the present invention;

[0032] In the figure, 100-stent body, 200-electrospinning nano drug-loaded fiber membrane, 300-hydrogel drug-loaded fiber membrane, 101-annular support member, 102-connecting member, 1021-first connecting part, 1022-second connecting part. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] like Figures 1 to 5 As shown, an embodiment of the present invention provides a shape memory sinus stent, comprising a stent body 100 and an electrospun nano drug-loaded fiber membrane 200 and a hydrogel drug-loaded fiber membrane 300 sequentially coated on the outer surface of the stent body 100; wherein the stent body 100 comprises a temporary shape and an initial shape, and the initial shape of the stent body 100 is composed of a plurality of annular support members 101 and a plurality of connectors 102 located between two adjacent annular support members 101; each annular support member 101 is in a sinusoidal wave structure, and the crests and troughs of the sinusoidal waves of two adjacent annular support members 101 correspond to each other, and the connector 102 connects the crests and troughs of the sinusoidal waves that are close to each other at every pair of corresponding crests and troughs, so that the initial shape of the stent body 100 is a cylindrical hollow structure;

[0035] The size of the temporary shape of the stent body 100 is smaller than the size of the initial shape of the stent body 100, and the shape memory sinus stent can be transformed from the temporary shape to the initial shape when subjected to external stimulation.

[0036] Sinus stents are usually made of degradable shape memory polylactic acid copolymers. However, the radial support strength of sinus stents formed by this material is poor and difficult to meet clinical needs. In addition to material modification, related technologies usually increase the wall thickness of the sinus stent to enhance the radial support strength of the sinus stent. However, excessive wall thickness of the sinus stent can easily lead to restenosis and neointimal hyperplasia in the sinus stent. Based on the above problems, Figure 1 As shown, in the embodiment of the present invention, the main structure of the sinus stent is firstly designed. The initial shape of the main structure is a cylindrical hollow structure, which is composed of a plurality of sinusoidal annular supports 101 of unequal height and a plurality of connectors 102 located between two adjacent annular supports 101. The crests and troughs of the sinusoidal waves of two adjacent annular supports 101 correspond to each other, and each pair of corresponding crests and troughs are connected by the connector 102. The stent body 100 of this structure has a strong radial support capacity and is not prone to brittle fracture.

[0037] Afterwards, an electrospun nano drug-loaded fiber membrane 200 and a hydrogel drug-loaded fiber membrane 300 for carrying different therapeutic drugs are sequentially arranged on the outer surface of the stent body 100. The electrospun nano drug-loaded fiber membrane 200 has a large specific surface area and a unique mesh structure, thereby being able to realize the controlled release function of the drug, and the hydrogel drug-loaded fiber membrane 300 has a high water content, high elasticity and a high specific surface area. When in use, the hydrogel drug-loaded fiber membrane 300 first contacts the inner wall of the human sinus, thereby being able to greatly reduce the discomfort and foreign body sensation of the human body. At the same time, due to its certain adhesion, it can also effectively avoid the problem of displacement or discharge of the sinus stent. In addition, through the design of the above structure, the drug can be administered at the first time after surgery, and sequential drug administration and intelligent controlled release of drugs can be realized. In addition, the sinus stent structure in the embodiment of the present invention has a personalized customization effect, and its size parameters can be adjusted according to the human sinus structure, so that it can fit well with the inner wall of the human sinus, thereby effectively avoiding the problem of displacement or discharge of the sinus stent.

[0038] At the same time, if Figures 3 to 4 As shown, the sinus stent in the embodiment of the present invention has shape memory properties. When the stent is in a temporary shape, its size is small and convenient for implantation. When subjected to external stimuli, the sinus stent can be transformed from the temporary shape to the larger initial shape. In the process of shape memory recovery, due to the resistance of the inner wall of the sinus, the shape memory sinus stent can fit completely with the inner wall of the sinus, reducing the patient's foreign body sensation.

[0039] According to some preferred embodiments, Figure 2 or Figure 3 The connecting member 102 includes a first connecting portion 1021 and a second connecting portion 1022, wherein the first connecting portion 1021 is "S"-shaped, and the second connecting portion 1022 is "V"-shaped, and two adjacent annular supporting members 101 are alternately connected through the first connecting portion 1021 and the second connecting portion 1022. The starting point and the end point of the "S"-shaped first connecting portion 1021 are respectively connected to the crest and the trough of the two adjacent supporting members, and the starting point and the end point of the "V"-shaped second connecting portion 1022 are respectively connected to the crest and the trough of the two adjacent supporting members.

[0040] Considering that the structure of the stent body 100 has a great influence on the radial support strength, bending stiffness, radial shrinkage rate and axial shortening rate of the sinus stent, in the embodiment of the present invention, Figure 2 or Figure 3As shown, by designing the annular support ring as a sinusoidal wave structure connected in sequence by "peak (trough)-trough (peak)", and the peaks and troughs of the sinusoidal waves of two adjacent annular support members 101 correspond to each other, the axial shortening rate of the bracket body 100 is effectively improved; the connecting member 102 is further designed as an "S"-shaped first connecting portion 1021 and a "V"-shaped second connecting portion 1022, and the "S"-shaped first connecting portion 1021 and the "V"-shaped second connecting portion 1022 are alternately connected to the peaks and troughs of the two adjacent upper and lower support members to improve the axial shortening rate of the bracket body 100, and when the distance between two adjacent rows of annular support members 101 is constant, the deformability of the bracket body 100 can be further increased, so that the bracket body 100 has sufficient bending and stretching space. At the same time, an open connection structure design is adopted between the "S"-shaped first connection part 1021 and the "V"-shaped second connection part 1022 and the adjacent annular support member 101, that is, the starting point and end point of the "S"-shaped first connection part 1021 and the "V"-shaped second connection part 1022 are respectively connected to the trough of the upper annular support member 101 and the peak of the lower annular support member 101, so as to further improve the bending stiffness of the bracket body 100.

[0041] According to some preferred embodiments, the heights of two adjacent wave peaks in the sine wave of each annular support member 101 are different.

[0042] In the embodiment of the present invention, Figure 2 As shown, by further designing two adjacent peaks of the sine wave in the annular support member 101 to have different heights, the annular support member 101 is made into an unequal height sine wave structure, which is beneficial to increase the angle of the annular support member 101 after expansion, thereby further enhancing the radial support strength of the stent body 100.

[0043] In order to make the stent body 100 conform to the size of the human sinus and provide better support for the inner wall of the sinus, and at the same time enable the drugs in the two layers of drug-loaded fiber membrane on the surface of the stent body 100 to be evenly released to the inner wall of the sinus after being implanted in the inner wall of the human sinus, the maximum diameter of the stent body 100 in the embodiment of the present invention is 10 mm.

[0044] According to some preferred embodiments, the degradation rates of the electrospun nano drug-loaded fiber membrane 200 , the hydrogel drug-loaded fiber membrane 300 , and the stent body 100 are different from each other.

[0045] In a further preferred embodiment, the degradation rates of the hydrogel drug-loaded fiber membrane 300 , the electrospun nano drug-loaded fiber membrane 200 , and the stent body 100 decrease in sequence.

[0046] Considering that the whole surgical wound healing process will go through three different stages, such as Figure 5As shown, in the embodiment of the present invention, by designing the arrangement order of the stent body 100, the hydrogel drug-loaded fiber membrane 300 and the electrospun nano drug-loaded fiber membrane 200 and the degradation rate of each layer, the hydrogel drug-loaded fiber membrane 300 and the electrospun nano drug-loaded fiber membrane 200 in the sinus stent can respectively achieve sequential drug administration and intelligent controlled release of drugs at different periods, and complete degradation in the body one after another. Specifically, in the first period after the implantation of the sinus stent, the soft hydrogel drug-loaded fiber membrane 300 in the outermost layer can achieve accurate and low-dose effective drug delivery at the first time after the operation to reduce the occurrence of postoperative inflammation, and can complete degradation within one month at the earliest; in the second period after the implantation of the sinus stent, the drug-loaded nanofiber membrane in the middle layer can further release drugs to treat the scar hyperplasia period, and then complete degradation within two months; finally, after the two layers of drug-loaded fiber membranes on the surface of the stent body are degraded, the stent body can still support the inner wall of the sinus to maintain nasal patency, prevent nasal adhesions, keep the sinus opening open, continuously inhibit inflammatory response, reduce postoperative adhesions and interventions, and finally complete degradation within three months.

[0047] In summary, through the design of the sinus stent structure, each layer and the degradation rate, the sinus stent can fully play its role in all periods after surgery, and the sinus stent will gradually degrade in the human body after promoting wound healing. The sinus stent will not be left in the sinus for a long time, reducing or eliminating the risk of potential complications. It is safer for the human body and avoids secondary surgery to remove the stent, which can effectively relieve pain and bring a better experience.

[0048] According to some preferred embodiments, the raw materials for preparing the stent body 100 include shape memory polylactic acid, biomedical polymer materials, and plasticizers; wherein the biomedical polymer material is at least one of glycolic acid-lactic acid copolymer, polycaprolactone, polyethylene glycol, polysuccinic acid co-succinate, polyglycolic acid, polytrimethylene carbonate, polypara-dioxanone or polyvinyl alcohol, and the plasticizer is at least one of vegetable oil-based plasticizers, plant-based plasticizers, bio-based plasticizers or citrate plasticizers.

[0049] In an embodiment of the present invention, the main material of the stent body 100 is a mixture of medical-grade shape memory polylactic acid and biomedical polymer materials. This not only makes the stent body 100 have better shape memory properties and better compatibility with the human body, but also can reduce the occurrence of inflammatory reactions and further reduce the foreign body sensation and discomfort caused by the stent body 100 being implanted in the human body.

[0050] At the same time, considering that the glass transition temperature of shape memory polylactic acid is relatively high when the shape memory sinus stent is driven by light or heat, in the embodiment of the present invention, a safe, non-toxic and degradable material is selected as a plasticizer and mixed with shape memory polylactic acid and biomedical polymer materials to reduce the glass transition temperature of the stent body 100 to 40-42°C, thereby reducing the discomfort caused to the human body when the sinus stent is stimulated.

[0051] According to some preferred embodiments, the raw materials for preparing the stent body 100 further include a driving agent, and the driving agent is at least one of hollow copper sulfide particles, gold nanoparticles, and carbon-based nanomaterials.

[0052] In an embodiment of the present invention, the sinus stent can be transformed by different external stimulation modes. Different driving modes include but are not limited to one or more of thermal drive, electric drive, magnetic drive, light drive, sound drive, solution drive, pH drive, etc. Considering the comfort to the human body, thermal drive or light drive is preferably selected as the driving mode of the sinus stent; when light drive is used, in order to make the stent body 100 have a light-responsive shape memory effect, a driving agent with high photothermal conversion efficiency is added to the preparation material of the stent body 100, and the light source for driving the shape memory sinus stent can be selected from near-infrared light or ultraviolet light.

[0053] According to some preferred embodiments, in the stent body 100, the content of shape memory polylactic acid is 70-90% (for example, it can be 70%, 80% or 90%), the content of biomedical polymer material is 10-30% (for example, it can be 10%, 20% or 30%), and the content of the plasticizer is 5-20% (for example, it can be 5%, 10%, 15% or 20%); in the stent body 100, the added amount of the driving agent is 0.2-0.5g (for example, it can be 0.2g, 0.3g, 0.4g or 0.5g).

[0054] In the embodiment of the present invention, the stent body 100 is prepared by mixing shape memory polylactic acid, biomedical polymer materials and plasticizers of appropriate types and contents, which is conducive to preparing a stent body 100 with good shape memory performance, biocompatibility and appropriate degradation rate.

[0055] According to some preferred embodiments, the raw materials for preparing the electrospun nano drug-loaded fiber membrane 200 include shape memory polylactic acid, biomedical polymer materials, additives and therapeutic drugs; wherein the additive is at least one of Centella asiatica, onion extract, chitosan, silk fibroin or chitosan, and the therapeutic drug is at least one of mometasone furoate, triamcinolone acetonide, budesonide, fluticasone propionate or beclomethasone propionate.

[0056] In the embodiment of the present invention, further combined with the period of postoperative wound healing, by adding specific types of additives and therapeutic drugs to the electrospun nano-drug-loaded fiber membrane 200, the above-mentioned types of additives can make the sinus stent have excellent effects such as promoting wound healing, anti-inflammation, anti-scarring, inhibiting fibroblast proliferation, promoting wound healing and promoting epithelialization. During the postoperative recovery process, the electrospun nano-drug-loaded fiber membrane 200 can controllably release therapeutic drugs to achieve the treatment of sinusitis.

[0057] It should be noted that in the embodiments of the present invention, additives and therapeutic drugs include but are not limited to the above-mentioned types, and the types can also be selected according to the actual treatment effects.

[0058] According to some preferred embodiments, in the electrospun nano-drug-loaded fiber membrane 200, the content of shape memory polylactic acid is 80-95% (for example, it can be 80%, 90% or 95%), the content of biomedical polymer materials is 5-20% (for example, it can be 5%, 15% or 20%), the content of additives is 5-10% (for example, it can be 5%, 8% or 10%), and the content of therapeutic drugs in the electrospun nano-drug-loaded fiber membrane 200 is 350-450μg (for example, it can be 350μg, 400μg or 500μg).

[0059] In the embodiment of the present invention, the electrospun nano-drug-loaded fiber membrane 200 is prepared by mixing shape memory polylactic acid, biomedical polymer materials, additives and therapeutic drugs of appropriate types and contents using an electrospinning method. This is not only beneficial for preparing the electrospun nano-drug-loaded fiber membrane 200 with good biocompatibility, but also beneficial for the electrospun nano-drug-loaded fiber membrane 200 to achieve controllable release of drugs within an appropriate degradation time, thereby treating the scar hyperplasia stage and achieving anti-scar and anti-inflammatory effects.

[0060] According to some preferred embodiments, the raw materials for preparing the hydrogel drug-loaded fiber membrane 300 include natural polymer materials and therapeutic drugs; wherein the natural polymer material is at least one of chitosan, silk fibroin, sodium alginate, gelatin, hyaluronic acid, chitin or collagen.

[0061] In the embodiment of the present invention, since the postoperative wound healing process will first experience an inflammatory period, the hydrogel drug-loaded fiber membrane 300 will first contact the inner wall of the sinus. Since the hydrogel drug-loaded fiber membrane 300 is relatively soft, it can greatly reduce the discomfort and foreign body sensation of the patient after surgery. By adding natural polymer materials during the preparation of the hydrogel drug-loaded fiber membrane 300, not only can the sinus stent have excellent effects such as hemostasis, accelerated wound healing, reduced postoperative inflammation, and prevention of postoperative adhesion, but also the sinus stent can be given better adhesion, thereby further avoiding the problem of displacement or expulsion of the sinus stent.

[0062] According to some preferred embodiments, the content of natural polymer materials in the hydrogel drug-loaded fiber membrane 300 is 80-100% (for example, it can be 80%, 90% or 100%), and the content of therapeutic drugs in the hydrogel drug-loaded fiber membrane 300 is 200-300μg (for example, it can be 200μg, 250μg or 300μg).

[0063] In the embodiment of the present invention, the hydrogel drug-loaded fiber membrane 300 is prepared by mixing natural polymer materials of appropriate types and contents with therapeutic drugs, which is not only conducive to preparing the hydrogel drug-loaded fiber membrane 300 with good biocompatibility and adhesion properties. At the same time, it is conducive to achieving controllable release of drugs in the hydrogel drug-loaded fiber membrane 300 within a suitable degradation time, thereby treating the inflammatory period, having the effects of hemostasis, accelerating wound healing, reducing postoperative inflammation, and preventing postoperative adhesion.

[0064] At the same time, it should be noted that in the embodiment of the present invention, a certain amount of additives can be added in the preparation of the hydrogel drug-loaded fiber membrane 300 according to actual treatment needs. The additive can be at least one of Centella asiatica, onion extract, chitosan, silk fibroin or chitosan, and the content of the additive can be 5-20%.

[0065] The embodiment of the present invention further provides a method for preparing the shape memory sinus stent as described in any one of the above items, the preparation method comprising the following steps:

[0066] (1) constructing a three-dimensional structural model of the initial shape of the stent body 100 according to the shape and size of the sinus structure;

[0067] (2) Shape memory polylactic acid is mixed with a biomedical polymer material to prepare a shape memory polymer, and the shape memory polymer is used as a printing line to perform 4D printing according to the three-dimensional structure model to obtain an initial shape of the stent body 100 (such as Figure 3 shown);

[0068] (3) The electrospinning method is used to prepare the electrospinning nano drug-loaded fiber membrane 200 and the hydrogel drug-loaded fiber membrane 300 respectively, and the electrospinning nano drug-loaded fiber membrane 200 and the hydrogel drug-loaded fiber membrane 300 are sequentially coated on the outer surface of the stent body 100 to obtain the shape memory sinus stent of the initial shape (such as Figure 1 and 5 shown);

[0069] (4) The shape memory sinus stent of the initial shape is heated to above the glass transition temperature, a load is applied, and the shape memory sinus stent of the temporary shape is obtained after cooling and shaping.

[0070] In the embodiment of the present invention, during use, before the shape memory sinus stent is implanted in the nasal cavity, temperature, electromagnetic or light stimulation is applied to the shape memory nasal stent in its initial shape, and an external force is used to transform the sinus stent in its initial shape, which is larger in size, into a sinus stent in a temporary shape, which is smaller in size (such as Figure 2 and Figure 3 As shown); then, the temporary shape of the sinus stent is implanted into the sinus, and external stimulation is applied to the temporary shape of the sinus stent, so that the temporary shape of the sinus stent is transformed into the initial shape of the sinus stent until it fits to the human nasal mucosa.

[0071] According to some preferred embodiments, the preparation method of the electrospun nano drug-loaded fiber membrane 200 is as follows: shape memory polylactic acid and biomedical polymer materials are added to an organic solvent and stirred to obtain a mixed solution; additives and therapeutic drugs are sequentially added to the mixed solution, and the mixture is stirred to obtain a spinning solution; the spinning solution is injected into a syringe, and the electrospun nano drug-loaded fiber membrane 200 is prepared by an electrospinning method; the organic solvent is dichloromethane;

[0072] The preparation method of the hydrogel drug-loaded fiber membrane 300 is as follows: adding a natural polymer material to an organic solvent and stirring and mixing to obtain a mixed solution; adding a therapeutic drug to the mixed solution and stirring and mixing to obtain a spinning solution; injecting the spinning solution into a syringe and preparing a natural hydrogel by an electrospinning method;

[0073] Adding a synthetic polymer material (freeze-dried gelatin-hydroxyphenylpropionic acid) into an organic solvent and stirring and mixing to obtain a mixed solution; adding a therapeutic drug into the mixed solution and stirring and mixing to obtain a spinning solution; injecting the spinning solution into a syringe and preparing a synthetic hydrogel by an electrospinning method;

[0074] The natural hydrogel and the synthetic hydrogel are mixed and cross-linked at room temperature to obtain the hydrogel drug-loaded fiber membrane 300 .

[0075] In the embodiment of the present invention, the electrospinning nano drug-loaded fiber membrane 200 and the hydrogel drug-loaded fiber membrane 300 can be made by the electrospinning process in the prior art, and at the same time, the parameters in the 4D printing process can be adjusted according to the actual application. However, it should be noted that when the hydrogel drug-loaded fiber membrane 300 is prepared by the electrospinning method, the cross-linking reaction of the relevant chemical groups in the fiber can be promoted by mixing the synthetic hydrogel with the natural hydrogel. In this way, the problem of poor mechanical properties of the hydrogel drug-loaded fiber membrane 300 caused by adding natural polymer materials to the preparation materials of the hydrogel drug-loaded fiber membrane 300 can be effectively avoided.

[0076] It should be noted that the freeze-dried gelatin-hydroxyphenylpropionic acid in the examples of the present invention can be purchased.

[0077] At the same time, taking into account the different treatment periods and different drug loading amounts, the thickness of the hydrogel drug-loaded fiber membrane in the embodiment of the present invention is less than the thickness of the electrospun nano drug-loaded fiber membrane. More specifically, the thickness of the hydrogel drug-loaded fiber membrane is 0.2-0.3mm, and the thickness of the electrospun nano drug-loaded fiber membrane is 0.4-0.5mm.

[0078] In order to more clearly illustrate the technical solutions and advantages of the present invention, a shape memory sinus stent and a preparation method thereof are described in detail through several embodiments below.

[0079] Embodiment 1:

[0080] (1) Using the modeling software Solidworks to construct a three-dimensional structural model of the initial shape of the stent body according to the shape and size of the sinus structure, and using the Cura software to slice the model to obtain a 3D printed structural model that can be printed;

[0081] (2) 85 g of shape memory polylactic acid, 5 g of plasticizer (tributyl citrate), and 10 g of biomedical polymer material (polycaprolactone) were added to the extruder and mixed to obtain a shape memory polymer, the extruder was preheated to 200°C, the traction machine speed was adjusted, and an extrusion line with a wire diameter of 1.75 mm was pulled out, and the collected extrusion line was installed on the 3D printer, and the constructed 3D printing structure model file was imported into the 3D printer, and the FDM printer was used for printing, and the printing parameters (temperature 190°C, speed 50%, fan speed 100%) were set to obtain the bracket body of the initial shape of the 4D printing;

[0082] (3) Preparation of electrospun nano drug-loaded fiber membrane: 8g of shape memory polylactic acid, 1.5g of biomedical polymer material (polycaprolactone) and 0.5g of additive (Centella asiatica) were added to an organic solvent (dichloromethane) and stirred for 12h to prepare a mixed solution with a concentration of 13wt%; 400μg of therapeutic drug (mometasone furoate) was added to 100mL of organic solvent (dichloromethane) and stirred to obtain a drug solution; the drug solution and the mixed solution were stirred for 4h to obtain a uniformly mixed drug-loaded spinning solution. 10mL of the drug-loaded spinning solution was poured into a syringe, the power supply was turned on, the voltage was set to 14kV, the propulsion speed was 3mL / h, the receiving distance was 20cm, the temperature was room temperature 25℃, and the humidity was 20% to obtain an electrospun nano drug-loaded fiber membrane.

[0083] Preparation of hydrogel drug-loaded fiber membrane:

[0084] 1.5 g of synthetic polymer material (lyophilized gelatin-hydroxyphenylpropionic acid) was dissolved in a mixed solvent of 10 mL of hexafluoroisopropanol and ultrapure water (9:1) to obtain a mixed solution; 250 μg of therapeutic drug (mometasone furoate) was added to the mixed solution, and the electrospinning solution was obtained after mixing; the electrospinning solution was placed in a 10 mL syringe installed on a microinjection pump, the voltage was set to 18 kV, the rate was 3 mL / h, and a drum collector (diameter 10 cm, width 20 cm, rotation speed 1000 n / min) was placed 18 cm away from the injector nozzle to collect random microfibers to obtain a synthetic hydrogel;

[0085] 1.5 g of natural polymer material (lyophilized gelatin) was dissolved in a mixed solvent of 10 mL of hexafluoroisopropanol and ultrapure water (9:1) to obtain a mixed solution; 250 μg of therapeutic drug (mometasone furoate) was added to the mixed solution and mixed to obtain an electrospinning solution; the electrospinning solution was placed in a 10 mL syringe installed on a microinjection pump, the voltage was set to 18 kV, the rate was 3 mL / h, and a drum collector (diameter 10 cm, width 20 cm, rotation speed 1000 n / min) was placed 18 cm away from the injector nozzle to collect random microfibers to obtain a natural hydrogel; the synthetic hydrogel and the natural hydrogel were mixed and cross-linked at room temperature for 3 h to obtain a hydrogel drug-loaded fiber membrane.

[0086] The electrospun nano drug-loaded fiber membrane and the hydrogel drug-loaded fiber membrane are sequentially coated on the surface of the stent body to obtain a shape memory sinus stent of the initial shape;

[0087] (4) Raise the temperature to heat the initial shape of the shape memory sinus stent to above the glass transition temperature Tg. When the surface temperature of the sinus stent is higher than Tg, the stent body will soften. At this time, apply a load to the softened sinus stent to make the sinus stent shrink to the middle into a temporary shape. Leave the heat source and wait for the surface temperature of the sinus stent to drop below Tg. After standing for a few minutes and removing the load, the shape of the sinus stent can be fixed, thereby obtaining a temporary shape memory sinus stent.

[0088] Embodiment 2:

[0089] (1) Using the modeling software Solidworks to construct a three-structure model of the initial shape of the stent body according to the shape and size of the sinus structure, and using Cura software to slice the model to obtain a 3D printed structure model that can be printed;

[0090] (2) 85 g of shape memory polylactic acid, 10 g of biomedical polymer material (polycaprolactone), 5 g of plasticizer (tributyl citrate) and 0.2 g of driver (gold nanoparticles) were added to an extruder and mixed to obtain a shape memory polymer, the extruder was preheated to 200°C, the traction machine speed was adjusted, and an extrusion line with a wire diameter of 1.75 mm was pulled out, and the collected extrusion line was installed on a 3D printer, and the constructed 3D printing structure model file was imported into the 3D printer, and the FDM printer was used for printing, and the printing parameters (temperature 190°C, speed 50%, fan speed 100%) were set to obtain a 4D printed initial shape of the bracket body;

[0091] (3) Preparation of electrospun nano drug-loaded fiber membrane: 8g of shape memory polylactic acid, 1.5g of biomedical polymer material (polycaprolactone) and 0.5g of additive (Centella asiatica) were added to an organic solvent (dichloromethane) and stirred for 3h to prepare a mixed solution with a concentration of 13wt%; 500μg of therapeutic drug (mometasone furoate) was added to 100mL of organic solvent (dichloromethane) and stirred to obtain a drug solution; the drug solution and the mixed solution were stirred for 4h to obtain a uniformly mixed drug-loaded spinning solution. 10mL of the drug-loaded spinning solution was poured into a syringe, the power supply was turned on, the voltage was set to 14kV, the propulsion speed was 3mL / h, the receiving distance was 20cm, the temperature was room temperature 25℃, and the humidity was 20% to obtain an electrospun nano drug-loaded fiber membrane.

[0092] Preparation of hydrogel drug-loaded fiber membrane:

[0093] 1.5 g of synthetic polymer material (lyophilized gelatin-hydroxyphenylpropionic acid) was dissolved in 10 mL of a mixed solvent of hexafluoroisopropanol and ultrapure water (9:1) to obtain a mixed solution; the electrospinning solution was placed in a 10 mL syringe mounted on a microinjection pump, the voltage was set to 18 kV, the rate was 3 mL / h, and a drum collector (10 cm in diameter, 20 cm in width, and a rotation speed of 1000 n / min) was placed 18 cm away from the injector nozzle to collect random microfibers to obtain a synthetic hydrogel;

[0094] 1.5 g of natural polymer material (lyophilized gelatin) was dissolved in a mixed solvent of 10 mL of hexafluoroisopropanol and ultrapure water (9:1) to obtain a mixed solution; 250 μg of therapeutic drug (mometasone furoate) was added to the mixed solution, and the electrospinning solution was obtained after mixing; the electrospinning solution was placed in a 10 mL syringe installed on a microinjection pump, the voltage was set to 18 kV, the rate was 3 mL / h, and a drum collector (diameter 10 cm, width 20 cm, rotation speed 1000 n / min) was placed 18 cm away from the injector nozzle to collect random microfibers to obtain a natural hydrogel; the synthetic hydrogel and the natural hydrogel were mixed and cross-linked at room temperature for 3 h to obtain a hydrogel drug-loaded fiber membrane;

[0095] The electrospun nano drug-loaded fiber membrane and the hydrogel drug-loaded fiber membrane are sequentially coated on the surface of the stent body to obtain a shape memory sinus stent of the initial shape;

[0096] (4) The shape memory sinus stent of the initial shape is heated to above the glass transition temperature Tg by near-infrared light irradiation. When the surface temperature of the sinus stent is higher than Tg, the stent body will soften. At this time, a load is applied to the softened sinus stent to make the sinus stent shrink to the middle into a temporary shape. The light source is removed and the surface temperature of the sinus stent is lowered to below Tg. After standing for a few minutes and removing the load, the shape of the sinus stent can be fixed, thereby obtaining a temporary shape memory sinus stent.

[0097] It has been found through experiments that the degradation rate of the shape memory sinus stent prepared in the above embodiments 1 to 2 is controllable, the hydrogel drug-loaded fiber membrane in the outermost layer can be degraded as early as within one month, the drug-loaded nanofiber membrane in the middle layer can be degraded within the second month, and the stent body in the innermost layer is degraded last, so that the sinus stent can fully play its role in all periods, and the sinus stent will gradually degrade in the human body, and the sinus stent will not be left in the sinus for a long time, reducing or eliminating the risk of potential complications, which is safer for the human body and avoids secondary surgery to remove the stent, which can effectively relieve pain and bring a better experience.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A shape memory sinus stent, characterized in that: It comprises a stent body and an electrospun nano drug-loaded fiber membrane and a hydrogel drug-loaded fiber membrane sequentially coated on the outer surface of the stent body; wherein the stent body comprises a temporary shape and an initial shape, and the initial shape of the stent body is composed of a plurality of annular support members and a plurality of connecting members located between two adjacent annular support members; each annular support member presents a sinusoidal wave structure, the crests and troughs of the sinusoidal waves of two adjacent annular support members correspond to each other, and the connecting members connect the crests and troughs of the sinusoidal waves that are close to each other every pair of corresponding crests and troughs, so that the initial shape of the stent body presents a cylindrical hollow structure; The size of the temporary shape of the stent body is smaller than the size of the initial shape of the stent body, and the shape memory sinus stent can be transformed from the temporary shape to the initial shape when subjected to external stimulation.

2. The sinus stent according to claim 1, characterized in that: The connecting member includes a first connecting portion and a second connecting portion, the first connecting portion is "S"-shaped, the second connecting portion is "V"-shaped, and two adjacent annular supporting members are alternately connected through the first connecting portion and the second connecting portion.

3. The sinus stent according to claim 2, characterized in that: The starting point and the end point of the "S"-shaped first connection part are respectively connected to the crest and the trough of two adjacent support members, and the starting point and the end point of the "V"-shaped second connection part are respectively connected to the crest and the trough of two adjacent support members.

4. The sinus stent according to claim 1, characterized in that: The heights of two adjacent wave peaks in the sine wave of each annular support member are different.

5. The sinus stent according to claim 1, characterized in that: The raw materials for preparing the stent body include shape memory polylactic acid, biomedical polymer materials, and plasticizers; wherein the biomedical polymer material is at least one of glycolic acid-lactic acid copolymer, polycaprolactone, polyethylene glycol, polysuccinic acid co-succinate, polyglycolic acid, polytrimethylene carbonate, poly-p-dioxanone, or polyvinyl alcohol, and the plasticizer is at least one of vegetable oil-based plasticizers, plant-based plasticizers, bio-based plasticizers, or citrate plasticizers; Preferably, the raw materials for preparing the stent body further include a driving agent, and the driving agent is at least one of hollow copper sulfide particles, gold nanoparticles, and carbon-based nanomaterials.

6. The sinus stent according to claim 5, characterized in that: The raw materials for preparing the electrospun nano drug-loaded fiber membrane include shape memory polylactic acid, biomedical polymer materials, additives and therapeutic drugs; wherein the additive is at least one of Centella asiatica, onion extract, chitosan, silk fibroin or chitosan, and the therapeutic drug is at least one of mometasone furoate, triamcinolone acetonide, budesonide, fluticasone propionate or beclomethasone propionate.

7. The sinus stent according to claim 6, characterized in that: The raw materials for preparing the hydrogel drug-loaded fiber membrane include natural polymer materials and therapeutic drugs; wherein the natural polymer material is at least one of chitosan, silk fibroin, sodium alginate, gelatin, hyaluronic acid, chitin or collagen.

8. The sinus stent according to claim 1, characterized in that: The degradation rates of the electrospun nano drug-loaded fiber membrane, the hydrogel drug-loaded fiber membrane and the stent body are different from each other.

9. The sinus stent according to claim 8, characterized in that: The degradation rates of hydrogel drug-loaded fiber membrane, electrospinning nano drug-loaded fiber membrane and stent body decrease in sequence.

10. A method for preparing a shape memory sinus stent according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: (1) constructing a three-dimensional structural model of the initial shape of the stent body according to the shape and size of the sinus structure; (2) mixing shape memory polylactic acid with a biomedical polymer material to obtain a shape memory polymer, and performing 4D printing according to the three-dimensional structure model using the shape memory polymer as a printing line to obtain a stent body of an initial shape; (3) preparing an electrospun nano drug-loaded fiber membrane and a hydrogel drug-loaded fiber membrane respectively by an electrospinning method, and coating the electrospun nano drug-loaded fiber membrane and the hydrogel drug-loaded fiber membrane on the surface of the stent body in sequence to obtain a shape memory sinus stent of an initial shape; (4) The shape memory sinus stent of the initial shape is heated to above the glass transition temperature, a load is applied, and the shape memory sinus stent of the temporary shape is obtained after cooling and shaping.

Citation Information

Patent Citations

  • Intracranial sirolimus medicament-release blood vessel stent and preparation method thereof

    CN101601616A

  • Drug-loaded hydrogel coating, and preparation method and application thereof

    CN105343939A

  • Thermoregulable shape memory polymer material and preparation method thereof

    CN107011647A

  • Nano particle-polymer injectable composite hydrogel double drug loading system and preparation method thereof

    CN107550921A

  • 4D-printing shape-memory-polymer-composite-material tracheal stent and preparing method thereof

    CN108969165A